2018
DOI: 10.1016/j.tcsw.2018.10.002
|View full text |Cite
|
Sign up to set email alerts
|

A conserved fungal hub protein involved in adhesion and drug resistance in the human pathogen Candida albicans

Abstract: Drug resistance and cellular adhesion are two key elements of both dissemination and prevalence of the human fungal pathogen Candida albicans . Smi1 belongs to a family of hub proteins conserved among the fungal kingdom whose functions in cellular signaling affect morphogenesis, cell wall synthesis and stress resistance. The data presented here indicate that C. albicans SMI1 is a functional homolog of Saccharomyces cerevisiae KNR4 and is invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 68 publications
(84 reference statements)
0
6
0
Order By: Relevance
“…[13][14][15][16] In the human fungal pathogen C. albicans, Knr4 has two homologs, Smi1 and Smi1B, that are involved in adhesion and antibiotic resistance. 17,18 These observations show that Kre6, Knr4, and their homologs have conserved roles in cell wall biogenesis among these fungi.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…[13][14][15][16] In the human fungal pathogen C. albicans, Knr4 has two homologs, Smi1 and Smi1B, that are involved in adhesion and antibiotic resistance. 17,18 These observations show that Kre6, Knr4, and their homologs have conserved roles in cell wall biogenesis among these fungi.…”
Section: Introductionmentioning
confidence: 73%
“…In the studies of Kre6 8 12 and Knr4 13 18 above, yeasts and wall composition were investigated by conventional fluorescence staining of cells or by extraction and isolation of components for chemical analysis. Infrared (IR) spectroscopy has been used to gain insight into cellular composition based on known IR absorption bands, many of which are distinct for various biocomponents: proteins, fats, and sugars, including chitin and glucans.…”
Section: Introductionmentioning
confidence: 99%
“…Strain that overexpress this protein has been found to have greater cell wall adhesion by many folds than the wild type strain. It is also involved in hyphal morphogenesis (Martin-Yken et al 2018 ). In C. albicans , the EAP1 gene (a putative cell-wall adhesin) has been identified, and in silico analysis indicated that it consists a signal peptide, a GPI-anchor site and has homology with various genes of many yeast encoding CWPs.…”
Section: Characterised Adhesins Of Common Opportunistic Human Fungal Pathogensmentioning
confidence: 99%
“…20,26,[28][29][30] Interestingly, KNR4 orthologs in C. albicans, SMI1 and SMI1B, are involved in pathogenesis and in biofilm resistance to antifungal agents. [31][32] Knr4 has two experimentally-confirmed properties out of the three required for a hub protein: it is at the crossroad of essential cellular pathways and it has a plethora of partners in the yeast PPI network. The third property required for Knr4 to be a hub in PPI networks is intrinsic structural flexibility.…”
mentioning
confidence: 99%
“…In eukaryotes, Knr4/Smi1 proteins are specific to the fungal kingdom and their deletion in the yeasts S. cerevisiae and C. albicans leads to hypersensitivity to certain antifungal agents. 11,[31][32] Targeting Knr4 interaction regions could lead to promising compounds that could be used in combinatorial therapies to reduce the high doses of antifungal agents currently required to control human pathogenic fungi. 37…”
mentioning
confidence: 99%